Cumulative distribution of ballistic impact failures of common twisted-pair data cables at orbital speeds. (February 2019) - Miller, Joshua E.; Read, Jon; Oliveras, Ovidio M.; Christiansen, Eric L.; Lear, Dana M.
Highlights: This paper documents a large volume of experimental work on the impact failure of a common spacecraft component the MIL-STD-1553 data cable. The paper describes the cable considered and the supporting configurations considered. The paper consolidates the obtained results into cumulative distribution functions for failure as in regions of experimental impact space both failed and passed cables may result depending on impact variations. Abstract: Data wire cable runs are a significant presence on the exterior of the International Space Station (ISS), and continued ISS mission support requires detailed assessment of cables due to micrometeoroid and orbit debris (MMOD) impact. These data wire cables are twisted-pair cables consisting of two 22AWG stranded conductors and fillers inside a tight fitting braided copper shield. The copper shield and its contents are covered with a jacket that has a nominal outer diameter of 3.76 mm and beta-cloth tape. The ISS engineering community has identified two loss-of-function mechanisms for these cables: open circuits due to severed conductors within the cable, and short circuits due to contact between conductors or grounded components. As these data cables are low power systems, short circuits are not expected to burn away the contact, so both open and short circuits are considered permanent loss-of-function for the cable. A total of ninety-seven impact experiments have been performed into these cables to develop a statistical model for the failure of these cables to be used in reliability studies. The experimental work has yielded cumulative distribution functions for these cables for steel and aluminum components of the orbital debris environment at representative speeds and impact obliquities.